Percutaneous Reconstruction of the Anterolateral Ligament of the Knee With a Polyester Tape - Wagih, Ahmad M. (Arthrosc Tech, 2016)
Recent advances in surgeons' understanding of the anatomic, biomechanical, and radiologic features of the anterolateral ligament (ALL) of the knee have led to an increased interest in reconstruction of this structure as part of the management of knee instability. Even without any technical flaws and proper positioning of the bone tunnels, there is a small subset of patients, approximately 7% of all patients, who experience some residual anterolateral rotational instability after anterior cruciate ligament reconstruction. For this reason, some researchers have turned again toward the anterolateral aspect of the knee and specifically the ALL. In this technical note, the surgical steps for percutaneous reconstruction of ALL of the knee using a polyester tape are described.